Integrasi Etika Filosofis dan Nilai-Nilai Profetik untuk Mewujudkan Pendidikan Islam yang Humanis, Adil, dan Transformatif - Ramadhan, Aji Rizqi; Said, Uswah Mujahidah Rasuna; Sauri, Sofyan; Afkar, Muhammad Faiqul (LP2M Universitas Islam Ahmad Dahlan, 2024)
This study explores integrating philosophical ethics and prophetic values ​​in Islamic education to realize humanistic, just, and transformative education. Philosophical ethics originate from human rationality and thought, while prophetic values ​​originate from Islamic teachings. By combining the two, Islamic education can be a vehicle for the formation of noble character, social sensitivity, spiritual intelligence, and intellectual skills. This study is qualitative, using a literature study approach and content analysis of related literature. The results of this study reveal that the relationship between philosophical ethics and prophetic values ​​prioritizes goodness, truth, good morals, good character, and humanitarian values, and the difference lies in the source of both. Philosophical ethics originate from socio-culture, human rational foundations, and other logics of goodness, while prophetic values ​​originate from religious teachings, namely the Qur'an and Hadith. Humanistic education glorifies human dignity and develops its potential as a whole. Fair education guarantees equal access and treatment without discrimination. Meanwhile, transformative education equips students as agents of positive change in society. This concept is expected to produce an intelligent generation with noble character. Apart from academic intelligence, education also aims to form a good personality and character following Islamic principles